Gravidez após transplante renal: interação entre a gestação e o enxerto - Ferreira,Cátia (2017)
Overview and aims: Kidney transplantation has brought a new hope to women with end stage renal disease (ESRD) who wish to become pregnant, as it can improve the reproductive function and restore fertility. A successful pregnancy after kidney transplant is possible, at expenses of high rates of maternal and fetal morbidity. The objective of the study is to investigate the impact of renal transplantation in obstetric and neonatal outcomes as well as the effect of pregnancy itself in the graft. Study design: Retrospective study and descriptive analysis Methods and population: Retrospective study of nine pregnancies in eight renal transplant recipients between 1995 and 2015 in Centro Hospitalar São João. We evaluated the pre-pregnancy and post-delivery renal function, outcomes of gestation, as well as maternal and fetal complications. Results: The average time between transplant and pregnancy was 51.1 ± 25.3 months. The most common complications were urinary tract infections (7 cases), preterm delivery (6 cases), fetal growth restriction (3 cases), and pre-eclampsia (2 cases). One case of intrauterine fetal death was recorded. The cesarean section rate was 66.7%. There were two cases of graft dysfunction, which resolved in the postpartum period, without rejection or graft loss. In one patient, graft dysfunction recurred five months post-delivery due to native kidney disease relapse. Currently, one year after delivery, her creatinine plasmatic level is 2.2 mg/dL. Conclusions: This study suggests that successful pregnancy is possible in renal transplant recipients. Neverthless, these pregnancies should be considered at high risk and we must be alert to the complications that may occur